Assessing The Impacts of Food and Mouth Disease Outbreak on The Indonesian Economy and Its Regional Growth - Sahara, Sahara; Sugema, Iman; Amaliah, Syarifah; Probokawuryan, Mutiara; Ahmad, Fahmi Salam (School of Business, Bogor Agricultural University (SB-IPB), 2023)
Foot and mouth disease (FMD) is typically endemic and commonly found as a recurring issue in many developing countries, including Indonesia. In 2022, FMD has massively spread to 62 districts and cities so that it was declared an outbreak which caused significant economic losses. In this paper, we attempt to assess the impacts of FMD on the Indonesian economy by using a computable general equilibrium (CGE) approach. The results show that the FMD outbreak caused negative pressure on national economic growth, reducing the real wage and consumption, as well as exacerbating trade deficit. The outbreak also induced higher prices of beef and dairy sectors as well as their related sectors. Based on the regional perspective, the main production regions of beef and dairy are expected to suffer higher economic loss than that of other regions. Meanwhile, at the household level, the outbreak caused considerable effect in lowering income and consumption, particularly for rural farm households. Some necessary policies to overcome the outbreak, consisting of establishing a FMD handling post, promoting vaccination, extending financial supports, and maintaining communication and transparency with other countries regarding the outbreak status. Keywords: Computable General Equilibrium (CGE), Foot and Mouth Disease (FMD), livestock, macroeconomy, regional